2017
DOI: 10.2340/00015555-2482
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cornified Envelope Proteins in Skin and Its Relationship with Atopic Dermatitis Phenotype

Abstract: Changes in the expression of cornified envelope (CE) proteins are thought to affect the development and course of atopic dermatitis (AD). The aim of this study was to examine the expression level of CE proteins in order to identify new molecular markers of the AD phenotype. Expression levels of CE proteins were evaluated in the skin of patients with AD (38 biopsies) and healthy subjects (26 biopsies). Levels of FLG, FLG2 and SPRR3 mRNAs and proteins were reduced in AD skin. Levels of LELP-1 and SPRR1A transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
30
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 29 publications
3
30
1
1
Order By: Relevance
“…Rinnerthaler et al [32] reported some similar changes with intrinsic ageing to those that we found in our cheek samples: decreased loricrin and SPRR 1A, 2E, S100A7, A8 and A9 levels. However, unlike the study of Trzeciak et al [33], we observed decreased levels of SPRR1A compared with their recorded increases in subjects with atopic dermatitis. Nevertheless, studying the hand eczema proteome, Molin et al [16] observed some similar changes to those reported here, that is increased SPRR2B, but also observed the opposite for other proteins, for example, reduced kallikrein 5 and increased S100A7-9 and 11.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Rinnerthaler et al [32] reported some similar changes with intrinsic ageing to those that we found in our cheek samples: decreased loricrin and SPRR 1A, 2E, S100A7, A8 and A9 levels. However, unlike the study of Trzeciak et al [33], we observed decreased levels of SPRR1A compared with their recorded increases in subjects with atopic dermatitis. Nevertheless, studying the hand eczema proteome, Molin et al [16] observed some similar changes to those reported here, that is increased SPRR2B, but also observed the opposite for other proteins, for example, reduced kallikrein 5 and increased S100A7-9 and 11.…”
Section: Discussioncontrasting
confidence: 99%
“…However, unlike the study of Trzeciak et al . , we observed decreased levels of SPRR1A compared with their recorded increases in subjects with atopic dermatitis. Nevertheless, studying the hand eczema proteome, Molin et al .…”
Section: Discussionmentioning
confidence: 41%
“…These findings provide evidence of the involvement of SERPINB3/SERPINB4 in skin inflammation. SPRR3 is a cornified envelope (CE) precursor protein that is virtually undetectable in normal skin . During the late stages of epidermal differentiation, the formation of the CE is essential for epidermal barrier function and involves the replacement of the plasma membrane by cross‐linkage of precursor proteins such as involucrin, SPRRs and loricrin.…”
Section: Discussionmentioning
confidence: 99%
“…The A-repeat shares homology with hornerin, whereas the B-repeat is reminiscent of filaggrin (Wu et al, 2009). Filaggrin 2 has been suggested to play a role in the maintenance of the epidermal barrier given its partial similarity to filaggrin (Wu et al, 2009), given the facts that its expression is affected in atopic dermatitis (Trzeciak et al, 2017) and it is rich in histidine and glutamine residues (Wu et al, 2009), sources of the natural moisturizing factors urocanic acid and pyrrolidone carboxylic acid, respectively (Hon et al, 2013). In addition, polymorphisms in the FLG2 gene have been found to be associated with the propensity to develop atopic dermatitis (Margolis et al, 2014).…”
Section: Discussionmentioning
confidence: 99%